Income disparity and economic growth: Evidence from China - Duo Qin; Marie Anne Cagas; Geoffrey Ducanes; Xinhua He; Rui Liu (Queen Mary University of London, Department of Economics, 2005)
This paper carries out a pilot empirical study on how income inequality affects growth and the macro economy by means of incorporating panel data information into a macro-econometric model. China is used as the pilot field. Provincial urban and rural household data are used to construct inequality measures, which are then used to augment household consumption equations in the ADB China model. Model simulations are performed to study the effect of inequality on GDP growth and its sectoral components. Results show that inequality is a robust explanatory variable of consumption and that the way inequality develops over time carries certain negative consequences on GDP and sectoral growth.
Keywords: R11; E21; D3; C5; C2; 330; Income inequality; Growth; Econometric model; China